New species of the Genus Haliclona (Haplosclerida: Chalinidae) from Korea - Kim, Hyung June; Lee, Sang-Hui; Kang, Dong Won (Zootaxa, 2017)
Two new marine sponges, Haliclona ieoensis sp. nov. and Haliclona sumenyoensis sp. nov. from the south Korea are described. Morphologically distinct from each other, both species are assigned to the genus Haliclona subgenus Haliclona. Haliclona ieoensis sp. nov. individuals are thickly encrusting to massive, beige colour and have small oscules flush on surface. Haliclona sumenyoesis sp. nov. individuals have a cylindrical tube with flexible stalk morphology, ivory colour, and large oscules. The description of these two new species brings the species of Haliclona (Haliclona) in Korea to five.